Retropharyngeal hematoma following anterior cervical spine surgery: Lessons from a case report (CARE-compliant). Issue 38 (September 2019) - Ren, Haiyong; Wang, Jin; Yu, Leijun
Abstract: Rationale: Retropharyngeal hematoma (RH) is an infrequent but potentially life-threatening complication of anterior cervical spine surgeries (ACSS). Challenging situations might be confronted and catastrophic events or even deaths still occurred occasionally during the treatment. Currently, no widely accepted protocol has been developed. Patient concerns: A 55 years old male underwent ACSS due to cervical myelopathy. Thirty-three hours after surgery the patient presented cervical swelling and obstructive dysphagia. Conservative treatment resulted in no recovery and cervical swelling progressed. Diagnoses: Emergent magnetic resonance imaging and plain radiograph established massive incisional and RHs. RH was shown to extend from the base of the skull to T1. Interventions: An emergent surgery was performed under local anesthesia and cervical hematoma was evacuated. Nonetheless, evacuation of the blood clots in the vision field resulted into incomplete recovery of throat blockage. A gloved finger was used to explore the retropharyngeal space and some hidden blood clots were found and evacuated, then the patient obtained complete relief of the symptoms. Outcomes: Normal respiration and swallowing functions were obtained after the surgery. Obviously, recovery of motor function was noted while no other complication was found at 3-month follow-up Lessons: Our case illustrated that dysphagia was an early symptom of RH. Posterior compression from RH could cause obstruction of the pharyngeal airway and lead to difficulty of intubation. Hematoma could spread through the retropharyngeal space, a hematoma exploration beyond the visual range might be necessary in some cases for fear of the hidden hematoma.